Prolongation Of Alpha Oscillations İn Auditory Oddball Paradigm - Öniz, Adile; BAŞAR, EROL (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2009)
Although an important component of the P300 target response is the "prolonged alpha response". no relevant analysis is found in the literature. The present study emphasizes the relevance of prolongation of alpha responses in auditory oddball paradigm. Two types of stimuli were applied to twenty subjects. As standard stimuli 80 dB-1500 Hz tones and the target stimuli 80 dB-1600 Hz tones were used. The prolongations of alpha responses were measured in 13 recording sites in the frequency range of 8-13 Hz. At the Cz recording site, the time period for reaching one third (duration of prolongation) of its peak-to-peak amplitude (1/3 latency) of alpha response to target was 446 ms. The prolongation of nontarget stimuli was 277 ms. Thus, the alpha response to target was significantly more prolonged than the alpha response to nontarget stimuli. Similarly, at C3, the alpha response to target stimuli was prolonged to 373 ms. The alpha response to nontarget stimuli was prolonged to 284 ms. The target alpha response was more prolonged in comparison to the non-target alpha results. The alpha response to target stimuli (431 ms) was also more prolonged in comparison with the alpha response upon non-target stimuli (266 ms) at the C4 recording site. The results indicate that the alpha responses are prolonged under a certain level of cognitive load and working memory. Alpha prolongation is a significant component of P300 responses. It can be Suggested that the cognitive load dependency of alpha responses upon the targets could be related to working memory. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: P300; EEG; ERP; alpha; oscillation; memory; cognition; high-resolution eeg; internally directed attention; event-related potentials; reaction time tasks; short-term-memory; working-memory; brain oscillations; prefrontal cortex; cognitive-processes; recognition memory; alfa; salınım; bellek; biliş; yüksek çözünürlüklü EEG; içten yönelik dikkati; olaya ilişkin potansiyeller; reaksiyon süresi görevleri; kısa süreli hafıza; çalışan bellek; beyin salınımlar; bilişsel süreçler; tanıma belleği